2017
DOI: 10.3199/iscb.12.13
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mutagenic effects of gamma irradiation on chilli (<i>Capsicum annuum</i> L.)

Abstract: The present study was carried out to induce cytological variations on Capsicum annuum L. (2n=24) var. Pusa Jwala by using various doses of gamma rays. Progenies were raised from the seeds of the selected cultivar treated with eight different doses of gamma rays, viz., 1, 5, 10, 15, 20, 25, 30 and 35 kR at Bhabha Atomic Research Centre, Mumbai. Cytological studies were carried out in the treated as well as in control materials. Gamma rays have shown a significant effect causing various types of chromosomal abno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
2
1
0
Order By: Relevance
“…The M 1 and M 2 generation results revealed that higher doses exhibited inhibitory effects on yield traits, while lower doses showed stimulatory effects on yield-attributing characters. These results agreed with previous studies ( Verma et al., 2017 ; Hanafy and Akladious, 2018 ; Naaz et al., 2020 ; ALshamrani et al, 2022 ). The diminution in quantitative traits at higher concentrations may arise due to physiological disturbance or DNA damage triggered in the plant cells by the mutagen ( Thilagavathi and Mullainathan, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…The M 1 and M 2 generation results revealed that higher doses exhibited inhibitory effects on yield traits, while lower doses showed stimulatory effects on yield-attributing characters. These results agreed with previous studies ( Verma et al., 2017 ; Hanafy and Akladious, 2018 ; Naaz et al., 2020 ; ALshamrani et al, 2022 ). The diminution in quantitative traits at higher concentrations may arise due to physiological disturbance or DNA damage triggered in the plant cells by the mutagen ( Thilagavathi and Mullainathan, 2011 ).…”
Section: Discussionsupporting
confidence: 94%
“…High estimate of heritability were recorded for number of branches per plant at harvest (74.08%), stem diameter (64.21%), leaf area (95.32%), days to rst owering (92.71%), sex ratio (64.45%) and number of fruits per plant (91.87%), while moderate estimate of heritability were observed for days to 50 per cent owering (41.22%), fruit weight (32.85%) and fruit yield per plant (57.34%), whereas, low estimate of heritability was found for vine length at harvest (16.20%) and fruit length (4.65%). The same heritability pattern was reported byShah et al (2015) in cucumber andVerma et al (2017) in chilli. This indicates the higher response for the selection of high yielding mutants as these characters are governed by additive gene actions and helps the plant breeder for making the effective selection.…”
supporting
confidence: 85%
“…Occurrence of micronuclei may be associated with the fragments and lagging chromosomes that could not reach the pole get involved with the daughter nuclei as recognized by Kumar and Dubey (1980). Disturbed polarity at telophase may cause due to disturbed spindle formation, also investigated by several workers as (Verma and Raina 1991) in Crotalaria juncea, (Verma and Sharma 2000) in Phlox drummondii., and (Verma et al 2017) in Capsicum annuum.…”
Section: Discussionmentioning
confidence: 96%